Direito ao meio ambiente e proibição do retrocesso - Mello, Paula Susanna Amaral (2013)
This paper aims at analyzing the fundamental right to integrity of the environment and obligations relating thereto in order to subsequently review the prohibition of environmental retrogression and limits thereof. The purpose of this paper is to contribute for the comprehension of the concept on prohibition of environmental retrogression, its scope and limits, avoiding vulgarization of the subject. Based on sound researches carried out on jurisprudence and case laws, this paper critically analyzes some of the key controversies involving prohibition of retrogression. A detailed study is conducted on fundamental rights theories, structure and applicability of such rights and obligations related thereto in order to finally choose the theoretical basis that best describes the national legal system reality. The environmental constitutional rule is classified as a principle and based on that conclusions are made on the relativity of its essential contend and of the ecological existential minimum. The origin and concept of the prohibition of environmental retrogression is deeply analyzed with emphasis on social rights, in which the doctrine acquired its more famous outline in order to critically analyze the approach the jurisprudence and case law have given to the matter in the environmental sphere. The conclusion is that the doctrine needs to be properly conceptualized in the environmental sphere, pointing out the nature of the prohibition of environmental retrogression as a legal limitation present in the third sub-rule of proportionality. The prohibition of environmental retrogression limits are analyzed in concrete cases